Katydids (Orthoptera: Tettigoniidae) of Gorongosa National Park and Central Mozambique - Naskrecki, Piotr; Guta, Ricardo (Zootaxa, 2019)
A list of 60 species of the Tettigoniidae (Orthoptera) recorded from Gorongosa National Park and provinces Sofala and Manica in central Mozambique is provided and their natural history is discussed. Of these, 58 species are illustrated and bioacoustic data are presented for 47 species. Two new genera and 9 new species are described: Gorongosa carri gen. et sp. n., Ovonotus abreuae gen. et sp. n., Afroagraecia muagurai sp. n., Enyaliopsis iaculator sp. n., Eurycorypha parkeri sp. n., Eurycorypha stalmansi sp. n., Eulioptera carolli sp. n., Eulioptera mutembai sp. n., and Parpyrrhicia guytonae sp. n. Four species of Ruspolia are recognized as potentially new and their bioacoustic data are presented. Pseudorhynchus pungens meridionalis Ragge, 1969 is synonymized with Pseudorhynchus pungens pungens (Schaum, 1853); Angustithorax spiniger Massa, 2015 is synonymized with Oxyecous magnus Ragge, 1956; and the synonymy of Lanista africana (Walker, 1870) with Lanista annulicornis (Walker, 1869) is reversed. Two species, G. carri and O. abreuae, appear to be endemic to Mt. Gorongosa and 24 species are recorded for the first time from Mozambique.